New records of bats from the northern region of the Peruvian Amazon - Díaz, María Mónica (2011)
The northern Amazon Basin in Peru is one of the most diverse areas for small mammals in the world. In this work, I present information related to the diversity of bat species in the Amazonian region of Iquitos, Peru, where nearly 60% of the 152 bat species known to Peru recorded. Unlike in previous investigations in this area, bat surveys were designed to detect species living in urban and rural areas. The results have added a new bat species (Eumops delticus) to the Peruvian fauna, eight new species for the region around Iquitos (Peropteryx macrotis, Peropteryx pallidoptera, Anoura caudifer, Lionycteris spurrelli, Vampyrum spectrum, Thyroptera lavali, Cynomops planirostris, and Molossus coibensis), and a new species for Northeast Peru (Eumops maurus).